Labour market modelling in the light of the financial crisis - Pierre Lafourcade; Andrea Gerali; Jan Brůha; Dirk Bursian; Ginters Buss; Vesna Corbo; Markus Haavio; Christina Håkanson; Tibor Hlédik; Gábor Kátay; Dmitry Kulikov; Matija Lozej; et al. (European Central Bank (ECB), 2016)
This paper revisits the empirical relationship between unemployment and output, and its evolution following the financial crisis of 2008, with the aim of drawing potential consequences for labour market modelling strategies in place within the European System of Central Banks (ESCB). First, the negative correlation between output and unemployment (Okun's law) at cyclical frequencies is found to be a robust feature of macro data across time, countries and identification schemes. Focusing on the euro area, the financial distress seems to have altered the dynamics of output and unemployment mainly at lower frequencies, interpreted as trend developments by the statistical filters used in the analysis. Looking at the implications for modelling strategies, we propose an extension of the standard labour search and matching model in which financial frictions impinge directly on the labour market rather than on the capital market, opening the way to protracted and lagged response of employment after a “financial” crisis. In terms of policy implications, the importance of the interplay between financial and labour market frictions in trend developments should be read as strong support for an ambitious structural reform agenda in Europe, so as to make our labour (and goods) markets more flexible and resilient.
Keywords: E1; E32; J64; 330; financial crisis; labour market; macroeconomic models of the labour market; output; unemployment